Youth unemployment and crime in France - Denis Fougère; Francis Kramarz; Julien Pouget (Institute for the Study of Labor (IZA), 2006)
In this paper we examine the influence of unemployment on property crimes and on violent crimes in France for the period 1990 to 2000. This analysis is the first extensive study for this country. We construct a regional-level data set (for the 95 départements of metropolitan France) with measures of crimes as reported to the Ministry of Interior. To assess social conditions prevailing in the département in that year, we construct measures of the unemployment rate as well as other social, economic and demographic variables using multiple waves of the French Labor Survey. We estimate a classic Becker type model in which unemployment is a measure of how potential criminals fare in the legitimate job market. First, our estimates show that in the cross-section dimension, crime and unemployment are positively associated. Second, we find that increases in youth unemployment induce increases in crime. Using the predicted industrial structure to instrument unemployment, we show that this effect is causal for burglaries, thefts, and drug offences. To combat crime, it appears thus that all strategies designed to combat youth unemployment should be examined.
Keywords: J19; K42; J64; J65; 330; crime; youth unemployment; Jugendarbeitslosigkeit; Soziale Lage; Kriminalität; Frankreich